Analisis Kerusakan Jalan Dengan Metode Pavement Condition Index Studi Kasus Jalan Raya Tanjungsari - Raya Tandes - Yordan Handhika Putra; Kurnia Hadi Putra (Institut Teknologi Adhi Tama Surabaya, 2023)
Highway Tanjungsari - Raya Tandes experienced some damage to the road sections which varied greatly from one point to another so that it required a detailed handling measure. Assessment of road damage can be done using several methods including the Pavement Condition Index (PCI) method.The purpose of carrying out this research task is to find out the value of the damage to the highawy Tanjungsari - Raya Tandes and how to deal with it. The results of the observations obtained 13 types of damage but with the most damage being holes and patches. The PCI value obtained is 3 segments with an average PCI value of 90 having a perfect value. 17 segments with an average PCI value of 70 have a very good value. 9 segments with an average PCI value of 66 have a good value. 8 segments with an average PCI value of 49 have an adequate value and 4 segments with an average PCI value of 31 have a poor value.